Praktek Kompensasi Persepsian Terhadap Perilaku Kewarganegaraan Organisasional (PKO) Berorientasi Pelayanan Dengan Koitmen Afektif Sebagai Pemediasi (Studi Kasus: Karyawan Rumah Sakit Swasta di Yogyakarta) - Putri, Eka Risma (Jurnal Ekonomi, 2013)
The purpose of this research to test empirically influence between compensation with organizational citizenship behavior (OCB) service-oriented. I used affective commitment as mediating variable. Setting this research at privat hospital in Yogyakarta. Respondent nurses with purposive sampling technique of sampling. I spread the qusestionaire to 255 nuses at two hospital. I use a hierarchical regression analysis to test the hypothesis. I found that the compensation persepption have a direct impact on service-oriented OCB, but through the mediation of affective commitment.